2023
DOI: 10.1371/journal.pone.0278134
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals increased abundance and diversity of opportunistic fungal pathogens in nasopharyngeal tract of COVID-19 patients

Abstract: We previously reported that SARS-CoV-2 infection reduces human nasopharyngeal commensal microbiomes (bacteria, archaea and commensal respiratory viruses) with inclusion of pathobionts. This study aimed to assess the possible changes in the abundance and diversity of resident mycobiome in the nasopharyngeal tract (NT) of humans due to SARS-CoV-2 infections. Twenty-two (n = 22) nasopharyngeal swab samples (including COVID-19 = 8, Recovered = 7, and Healthy = 7) were collected for RNA-sequencing followed by taxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…It was also seen that opportunistic pathogens like Candida sp. increased in abundance 26 . In our analysis, we found that the alpha diversity was lower ( p < 0.05) between the healthy cohort and the SCT2 cohort.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…It was also seen that opportunistic pathogens like Candida sp. increased in abundance 26 . In our analysis, we found that the alpha diversity was lower ( p < 0.05) between the healthy cohort and the SCT2 cohort.…”
Section: Discussionmentioning
confidence: 42%
“…increased in abundance. 26 In our analysis, we found that the alpha diversity was lower (p < 0.05) between the healthy cohort and the SCT2 cohort. These were the group of patients who had received systemic corticosteroids, antibiotics, and antivirals.…”
Section: Compositional Variations Of Nasal Mycobiome Among the Groupsmentioning
confidence: 53%
“…To overcome this problem, we analyzed Kraken2 output with Bracken2 (Bayesian Re-estimation of Abundance after classification with KrakEN), which uses the taxonomy assigned by Kraken2 to estimate the number of reads per sample that come from different species, using the Kraken report output file. 13 , 14 , 15 , 16 , 17 The Kraken2 database was utilized to construct a Bracken-compatible database using the Bracken build function. An in-house Python program was written to combine the output from the bracken report file and add lineage information and convert it into a biom file using Kraken-biome to import into R for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“… 13 Many studies have demonstrated the superiority of commensal microbial composition over opportunistic pathogens in the early recovery of COVID-19 patients. 14 , 15 , 16 These findings suggest the importance of understanding the dynamics of TAMs in longitudinal studies with respect to the COVID-19 patients who were exposed to the virus during several waves, and if so, how this could be coupled to the severity of the disease and the patients' clinical outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…6,7 In addition to its recognized use in treating chronic diseases, individualized homeopathy may also be effective in resolving or managing acute cases, including epidemic diseases. 8,9 However, it is important to emphasize that the use of customized homeopathy requires precise diagnosis and treatment to ensure its efficacy and safety. In epidemic diseases, which often present similar symptomatology in affected individuals, the individualized homeopathic medicine should be selected based on the signs and symptoms that the patient presents at different stages or phases of the outbreak.…”
mentioning
confidence: 99%